Simulation calculation of 3D electric field and natural flashover analysis of ice‐covered silicone rubber insulator - Bingbing Dong; Yuyao Hu; Fanghui Yin; Xingliang Jiang (IET Generation, Transmission & Distribution, 2023)
Abstract The effects of uneven icing, number of icicles, inclination angle of icicle, ice pallets and arc ignition on the electric field are ignored for the two‐dimensional axisymmetric model of ice‐covered insulator. Therefore, a 3D simulation model was developed in this paper. The average electric field strength of air gap (Eav) and maximum field strength of icicle tip (Emax) were determined to characterize the influence of various factors on the electric field distortion degree. The results show that compared with the insulator without ice and with a dry ice, the supply voltage is almost entirely applied to all icicle air gaps for a wet ice‐covered insulator. Eav is independent of icicle diameter and icicle number but increases with the increment of icicle length and icicle inclination angle. Emax raises with the increase of icicle length, icicle number, icicle inclination angle and icicle diameter. As the source of electric field distortion, the ice pallets on the surface of the sheds rise the field strength of air gap. Based on the simulation analysis and natural icing test, the applied voltage is redistributed in the remaining air gaps when an arc occurs in the gap near the high‐voltage terminal, thereby causing the subsequent flashover.